Cloud computing, security, privacy in new computing environments : 7th International Conference, CloudComp 2016, and first International Conference, SPNCE 2016, Guangzhou, China, November 25-26, and December 15-16, 2016, Proceedings /: 7th International Conference, CloudComp 2016, and first International Conference, SPNCE 2016, Guangzhou, China, November 25-26, and December 15-16, 2016, Proceedings. (2018) - Unknown
No abstract available